A second gene for the African green monkey poliovirus receptor that has no putative N-glycosylation site in the functional N-terminal immunoglobulin-like domain. - Koike, S (1992)
Using cDNA of the human poliovirus receptor (PVR) as a probe, two types of cDNA clones of the monkey homologs were isolated from a cDNA library prepared from an African green monkey kidney cell line. Either type of cDNA clone rendered mouse L cells permissive for poliovirus infection. Homologies of the amino acid sequences deduced from these cDNA sequences with that of human PVR were 90.2 and 86.4%, respectively. These two monkey PVRs were found to be encoded in two different loci of the genome. Evolutionary analysis suggested that duplication of the PVR gene in the monkey genome had occurred after the species differentiation between humans and monkeys. The NH2-terminal immunoglobulin-like domain, domain 1, of the second monkey PVR, which lacks a putative N-glycosylation site, mediated poliovirus infection. In addition, a human PVR mutant without N-glycosylation sites in domain 1 also promoted viral infection. These results suggest that domain 1 of the monkey receptor also harbors the binding site for poliovirus and that sugar moieties possibly attached to this domain of human PVR are dispensable for the virus-receptor interaction.